Cited! : identifying credible information online - Gerber, Larry, 1946- (Digital and information literacy., 2018)
In an online world where the amount of information seems to increase exponentially even week to week, student researchers can find it an ever-greater challenge to distinguish credible, vetted content from hearsay and misinformation. This volume on citing internet sources will help them determine which online sources are trustworthy and which are not. Its lively and engaging instructional tips will help readers successfully negotiate the vast landscape of information out there. They will produce quality research for papers now and beyond in their academic careers with skill and confidence.